Exergy analysis on a thermoelectric heat recovery device with an exhaust gas heat source from a combustion engine - Sarwo Edhy Sofyan; Pratama, Yudha; Khairil, Khairil (Journal of Mechafa Engineering and Fabrication, 2025)
An internal combustion engine converts thermal energy into mechanical work with an efficiency of approximately 35–40%, depending on the engine type and operating conditions. This indicates that about 60–65% of the total energy is wasted, primarily in the form of heat loss through the cooling system, exhaust gases, and mechanical friction. One potential approach to improve engine efficiency is by recovering waste heat using a thermoelectric generator (TEG) system. This study aims to analyze the exergy performance of a thermoelectric heat recovery system that utilizes exhaust gas heat from an internal combustion engine as an energy source. The analysis focuses on the influence of engine speed variation and aluminum fin configuration on the exergy value, exergy destruction, and exergy efficiency to enhance waste heat utilization. The heat recovery system is connected to the exhaust pipe outlet, and several fin configurations are investigated: left–left-right, top–bottom, all-sided, and without fins. Tests were conducted at engine speeds of 1300, 1600, 1900, and 2200 rpm to observe variations in energy distribution and efficiency. The results indicate that the exergy value generated by the thermoelectric heat recovery system increases with higher engine speed. This finding demonstrates that the proposed system can effectively improve the thermal efficiency of internal combustion engines by converting exhaust heat into useful energy, contributing to overall energy savings and the development of more efficient energy conversion technologies.